Evaluación de la vacuna antignrh sobre la fertilidad e histología reproductiva en cobayos - Guamán Chimbo, Dayana Carolina (2025)
Immunocastration is a non-surgical castration method that uses an anti GnRH vaccine to inhibit reproductive function. Therefore, the study addresses the use of immunocastration as an alternative to traditional castration methods in guinea pigs, aiming to reduce stress, pain, and complications associated with surgical techniques. The research was conducted in Guaranda, Ecuador. The study methodology included 45 guinea pigs divided by sex and treated with different vaccine doses (saline solution, 0.2 ml, and 0.5 ml of anti GnRH vaccine). Variables such as weight, body length, gonadal morphometry, estrous cycle, and adverse effects were measured. Castration was performed on all males to remove one testicle and study the effects of the vaccine at a histological level. The results showed that the vaccine did not significantly affect the weight or body length of the guinea pigs during the first few weeks. However, histological analysis revealed alterations in the seminiferous tubules, indicating a decrease in reproductive function. Additionally, a reduction in birth rate was observed, confirming the vaccine's efficacy for population control. Adverse effects included lacerations at the application site, but these did not compromise the animals' overall health. The study concludes that the anti GnRH vaccine, at a dose of 0.2 ml, showed a more favourable balance in terms of efficacy and functionality. However, it highlights the importance of further research to adjust the doses and reduce possible adverse effects, thus improving its safety and effectiveness.